Factors influencing teaching higher-order thinking skills among mathematics teachers in Malaysian primary schools - Chandran, Tamilarasi; Kamarudin, Nurzatulshima; Mustakim, Siti Salina; Silvarajan, Lavanya; Zaremohzzabieh, Zeinab (Universiti Putra Malaysia Press, 2023)
Integrating higher-order thinking skills (HOTS) into the mathematics curriculum has been a longstanding goal of the Malaysian education system. By recognizing its growing importance in enhancing students’ thinking abilities, this study explores the factors influencing the teaching of HOTS in primary schools across Malaysia. A quantitative research approach is used to analyze 269 randomly selected mathematics teachers from primary schools in Temerloh, Malaysia, to investigate the impact of four influencing factors: teachers’ knowledge of HOTS, pedagogical skills, attitude, and barriers to teaching HOTS. The findings from this study revealed that all four influencing factors significantly predict the teaching of HOTS among Malaysian mathematics teachers. These results hold significant promise in enriching teaching practices and fostering HOTS integration within the school context. By providing valuable insights into the dynamics of teaching HOTS, this study aims to equip teachers, schools, and administrators with essential resources to enhance students’ academic achievements. The implications of this research are far-reaching and hold the potential to revolutionize the learning and teaching landscape in Malaysia, not only in mathematics but also in other disciplines, thereby elevating the overall learning experience.